Analysis of Disparities in Fiscal Needs and Capacity in Central Lombok Regency Before and After the Implementation of the Mandalika Special Economic Zone - Erika Purnami; Hailuddin Hailuddin; Eka Agustiani (Future Techno-Science, 2025)
This study aims to determine the disparity between the fiscal needs and capacity of the Central Lombok Regency before and after the existence of the Mandalika Special Economic Zone (SEZ). This study uses a comparative descriptive method with a quantitative approach and uses secondary data. The data analysis method uses fiscal needs analysis tools, fiscal capacity, average disparity of fiscal needs and capacity, regional financial independence ratio, regional financial dependency ratio and regional financial decentralization degree ratio. The results of the study indicate that the fiscal needs before and after the existence of the Mandalika SEZ are on average higher after the existence of the Mandalika SEZ, while for the fiscal capacity, the average amount is constant both before the existence of the Mandalika SEZ and after the existence of the Mandalika SEZ, so that the disparity between fiscal needs and fiscal capacity after the existence of the Mandalika SEZ is on average higher than before the existence of the Mandalika SEZ, which means that the financial capacity of the regional government is decreasing to finance its financial needs. This is also reflected by the average low level of independence followed by a very high level of dependency and a very low degree of fiscal decentralization. This situation illustrates that the Central Lombok Regency Government is still very dependent on transfer funds from the central government. To reduce the level of dependency, the Central Lombok Regency Government must optimally explore PAD sources.